Impact of Transplantation of Cryopreserved and Preincubated with Thymic Multipotent Stromal Cells of Hemopoietic Stem Cells Lethally Irradiated Mice Survival - Nikolska, Kateryna I. (Problems of Cryobiology and Cryomedicine, 2019)
Survival and average life expectancy of 128 CBA mice, intravenously injected the next day after lethal irradiation with 0.5 × 106 cryopreserved syngeneic bone marrow cells (BMCs) or cryopreserved syngeneic cells of fetal liver (FLCs) of 14 days of gestation were studied. In some experiments, the cells were incubated in vitro after thawing for 20 hrs with multipotent stromal cells (MSCs) of thymus. It has been established that the contact interaction with thymic MSCs significantly increases the survival of mice as a result of transplantation of hematopoietic stem cells (HSCs) and progenitors of different degrees of maturity. The use of bone marrow cells preincubated with thymic MSCs enhances the survival of irradiated mice at the late post-irradiation stage (after 14–16 weeks that was 13% of the survived animals with 0% in the control). Application of fetal liver cells preincubated with thymic MSCs increases the murine survival rate at the early stage (after 4 weeks it was 40% with 18% in the control) and in 2.4 times prolong the average life expectancy of animals. The results can be used to improve the HSC transplants and methods for their application. Probl Cryobiol Cryomed 2019; 29(2):115–124.